Automobile braking and traction characteristics on the different road surfaces - Sokolovskij, Edgar (Transport, 2007)
The present article depicts the results of the investigation into automobile braking parameters and traction characteristics on the different road surfaces. The results of the investigation into automobile braking (the automobile deceleration and coefficient of traction), while braking in winter conditions, i.e. on ice and snow, are presented. The values of deceleration of the automobile while braking on various non‐typical surfaces, on the asphalt, covered with the motor oil or resin, while driving across the petrol spot, and on other surfaces of the road, are presented. Such data are necessary while modelling the automobile’s movement in various road conditions and while carrying out the examination of traffic accidents. First Published Online: 27 Oct 2010